Impact of NPA on the Profitability of Banks – with special references to Indian Banks - Dr. Anshu Tyagi, Dr. Kamini Rai, Dr. Meenakshi Sharma (International Journal of Advanced Science and Technology, 2020)
The growth of the economy depends upon the efficiency and stability of the banking sector. The most important factor which measures the health of the banking industry is the size of NPAs. Non-Performing assets have direct impact on the financial performance of banks i.e. their profitability. This paper attempts to first examine the level of NPAs in the public sector and Private sector banks in India and then its impact on the profitability of the banks.The secondary data collected from different source has been used in the study. The study shows that the magnitude of NPAs is increasing in the private sector and the public sector banks. Therefore banks need to effectively control their NPAs in order to increase their profitability and efficiency.